A Psychoeducational Application on Sexual Education to Prevent Child Sexual Abuse in Elementary School - Murfiah Dewi Wulandari; Ika Candra Sayekti; Muhammad Mus'ab; Oktadella Maulida Nur Isnaindita; Alfiah Sri Murni Wulandari (Universitas Pendidikan Ganesha, 2025)
Child sexual abuse (CSA) is a global issue that threatens children’s safety and psychological development. Many elementary school students still have limited knowledge and skills to protect themselves, while sex education is often considered a sensitive topic in various social and cultural contexts. This study aims to develop and test the effectiveness of a psychoeducational digital application as a sex education medium to improve children’s self protection skills. This research employed the ADDIE development model and involved elementary school teachers and students as research participants selected through purposive sampling. Data were collected using expert validation sheets, the System Usability Scale (SUS) questionnaire, black box testing sheets, and the What If Situations Test (WIST III) instrument. Data were analyzed using descriptive statistics, paired samples t-test, and N-Gain scores. The results show that the developed psychoeducational digital application integrates behavioral skills training in recognizing, refusing, and reporting unsafe situations. The application was considered valid, had good usability, and all functions operated properly. In addition, the use of the application significantly improved students’ self protection skills. In conclusion, the psychoeducational digital application is effective in improving children’s self-protection skills against sexual abuse. The implication is that this application can be utilized as an innovative learning medium to support children’s sex education both at school and at home.